The prevalence of mild cognitive impairment with type 2 diabetes mellitus among elderly people in China: A cross-sectional study - Gao, Yuxia; Xiao, Yanyu; Miao, Rujuan; Zhao, Jiangang; Cui, Mingfei; Huang, Guowei; Fei, Ma (Archives of gerontology and geriatrics, 2016)
•Higher prevalence for MCI with T2DM among Chinese elderly community-based population aged 65 years and older.•The risk factors for MCI with T2DM included current smoking, duration from onset of diabetes, FPG, HbA1c and IRI.•T2DM is significantly associated with a higher risk of MCI and may aggravate the clinical picture as a concomitant factor. In absence of curative treatments for dementia with type 2 diabetes mellitus (T2DM), mild cognitive impairment (MCI) in T2DM, the preclinical transitional states of dementia with T2DM has attracted dramatic attention. Our study was to estimate the prevalence and distribution of MCI in T2DM subjects from China, and identify influencing factors of subjects in MCI with T2DM. In the present study, we performed cluster random sampling of 8213 people aged 65 years and older in Tianjin, a metropolitan city, located in northern China. All participants were interviewed and screened for T2DM. 1109 subjects with T2DM were initially screened with American Diabetes Association criteria for diagnosis of diabetes mellitus and were diagnosed with MCI and dementia according to the criteria of DSM-IIIR. The prevalence of MCI and dementia in subjects with T2DM were compared with that in ordinary subjects. Logistic regression analyses were performed to evaluate risk of MCI with T2DM. Among all 8213 subjects, overall MCI and dementia with T2DM prevalence were 13.5% and 2.34%, respectively. Compared with ordinary subjects, the prevalence of MCI in the present study was more frequent than the prevalence of MCI for the general population in almost each age group. In the univariate analyses, among all diabetic subjects, compared with cognitive intactly subjects, MCI subjects had significantly higher levels of age, current smoking, mean waist circumference, duration from onset of diabetes, insulin intake, systolic BP, fasting plasma glucose (FPG), glycosylated hemoglobin (HbA1c) and immunoreactive insulin (IRI). In multivariate logistic regression analyses, variables including current smoking, duration from onset of diabetes, FPG, HbA1c and IRI were significantly associated with increased risk for MCI with T2DM, the ORs were 1.36,1.33,1.17,1.25 and 1.33, respectively (all P<0.05). The present study confirms the high prevalence of MCI with T2DM among the elderly population of China. T2DM is related to a higher risk of MCI in a population with a high prevalence of this disorder and may aggravate the clinical picture as a concomitant factor.